Biology, ecology and fishery practices of sea urchin in sabah - Raymie, Nurhasan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Sea urchins are spiny animals in the Phylum Echinodermata and the roe is a highly prized delicacy in selected countries. In Malaysia, scientific documentation on sea urchins is scarce and this baseline knowledge is urgently needed for conservation, proper management of sea urchin natural stocks and to fill in the gap of sea urchin information in Malaysia. Therefore, a study was conducted from December 2010 until November 2011 at selected districts in Sabah which is the only state in Malaysia that has sea urchin fishery industry. This study aims to document the morphological description of species found, biodiversity, population, gut content, reproductive biology and fishery practices of sea urchin in Sabah waters. Morphological descriptions of each sea urchin species found were based on its test, ambulacra, interambulacra, apical system, peristome, spine and colour while specific behaviour and habitat of sea urchin were also noted during field sampling. A total of ten species were found namely Phyllacanthus imperialis, Diadema setosum, D. savignyi, Echinothrix calamaris, Mespilia globulus, Salmacis sphaeroides, Echinometra mathaei, Pseudoboletia maculata, Toxopneustes pileolus and Tripneustes gratilla. A total of 29 sampling sites from six districts (Tawau, Semporna, Lahad Datu, Sandakan, Kudat and Kota Belud) were involved in population study, but only 18 sites recorded the presence of sea urchins with D. setosum as the most dominant species in Sabah waters. Overall, Semporna showed the highest species composition of sea urchin among other districts. All ten sea urchin species found in Sabah were analysed for general gut content analysis. Food materials ingested by sea urchins can be distinguished into six categories namely seagrass, seaweed, hard surface, bottom material, hard animal and unidentified material. The reproductive biology of D. setosum was studied using Gonadal Somatic Index (GSI) and it was revealed that D. setosum spawned continuously throughout the year. However, the GSI values of D. setosum were found to be influenced by moon phase and spawned during full moon. Six edible sea urchin species were identified in this study namely D. setosum, D. savignyi, T. gratilla, E. calamaris, P. maculata and T. pileolus, with D. setosum and T. gratilla are the main marketed species. Sea urchin fishery industry in Sabah was operated at small-scale for domestic market only. Semporna was identified as the main district in Sabah that harvests and markets sea urchin the most. As a conclusion, this study provides useful and important information on the current status of sea urchin resources and fishery in Sabah. These findings may contribute towards a more sustainable sea urchin stocks management and aquaculture potential. Although sea urchin fishing industry was operated at a small-scale, this industry has high potential to be developed with proper juvenile production technology for important fishery species.